STATUS OF HAEMORRHAGIC SEPTICAEMIA BASED ON EPIDEMIOLOGY IN PAKISTAN - U. FAROOQ, M. HUSSAIN1, H. IRSHAD, N. BADAR, R. MUNIR AND Q. ALI2 (Pakistan Veterinary Journal, 2007)
Haemorrhagic septicaemia (HS) was recorded by prevalence and importance percentages in Pakistan using various procedures of Participatory Disease Surveillance. The data obtained were analyzed to identify the high risk and low risk areas for HS in Pakistan. The highest prevalence (49.00%) was recorded in Khanewal district, while lowest (0.78%) was recorded in Jamshaid Saddar (Karachi). Highest importance (75.64%) was recorded in Faisalabad district, while lowest (1.53%) was recorded in Bajaur agency.